Our children can see that we aren't the only wee school in the countryside: can shared teachers offer solutions to the challenges facing rural primary schools in a divided society?. Issue 1 (2nd January 2021) - Bates, Jessica; McCully, Alan
Abstract : This paper examines the experience of Shared Teachers (STs) who were employed on temporary contracts across school partnerships designed to enrich and integrate the educational experiences of children in primary schools in rural and religiously diverse areas in Northern Ireland, as part of a specific Shared Education Programme. In a society emerging from conflict, where Shared Education is advocated both to improve the quality of education and contribute to more positive community relations, this paper critically explores the strengths and limitations of using a ST initiative to develop inter-school collaboration. There were clear educational benefits in sharing resources, planning and curricular enrichment but the potential to affect positive community relations was often limited. STs were used for routine tasks within individual partnership schools, rather than normalising shared experience where pupils are educated together. STs lacked the institutional support necessary to challenge the cultural and social mores embedded within a divided society.